FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEMAMPUAN MENGONTROL ELIMINASI DEFEKASI PADA ANAK USIA 1-3 TAHUN DI PAUD MUSTIKA SEKERNAN KECAMATAN SEKERNAN TAHUN 2012 - Suryati Suryati (Universitas Batanghari Jambi, 2014)
Eliminasi defekasi practice is growth duty of child under five years age. Control by ani spincter tired toddler age. Control defekasi eliminasi require to be trained. failure of practice defekasi eliminasi can cause trouble conception self at child. 74 % child in PAUD Mustika Sekernan still not yet doing defekasi eliminasi practice. This research aim to know relation readiness of child physical, and readiness of old fellow with ability control defekasi eliminasi at toddler age child. This Research type is quantitative with cross sectional desain. research at PAUD Mustika Sekernan in July 2012. Sample is all of PAUD pupil amounting to 35 child people. Result of research known by there is relation is readiness of parent and readiness of child physical to ably control defekasi eliminasi at child. Readiness of child physical with p-value=0,0,028(<0,05), readiness of parent that is parent of knowledge p-value=0,015(<0,05 ) parent of atittude p-value=0,012(<0.05), and parent of action p-value=0,099(<0,05). Is thereby expected to parent which is its child have been able to in readiness of physical so that defekasi eliminasi practice to its child. Beside that knowledge, parent of action and attitude in teaching defekasi eliminasi practice of vital importance to efficacy of child in controlling defekasi eliminasiKeyword : capabilities, elimination, child